2020
DOI: 10.3390/cancers12030667
|View full text |Cite
|
Sign up to set email alerts
|

The Bradykinin-BDKRB1 Axis Regulates Aquaporin 4 Gene Expression and Consequential Migration and Invasion of Malignant Glioblastoma Cells via a Ca2+-MEK1-ERK1/2-NF-κB Mechanism

Abstract: Glioblastoma multiforme (GBM) is the most common form of brain tumor and is very aggressive. Rapid migration and invasion of glioblastoma cells are two typical features driving malignance of GBM. Bradykinin functionally prompts calcium influx via activation of bradykinin receptor B1/B2 (BDKRB1/2). In this study, we evaluated the roles of bradykinin in migration and invasion of glioblastoma cells and the possible mechanisms. Expressions of aquaporin 4 (AQP4) mRNA and protein were upregulated in human glioblasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…Then, primary rat osteoblasts were treated with 25, 50, and 100 μM MPP for 24 h or 100 μM MPP for 6, 12, and 24 h. Morphologies of osteoblasts were observed and photographed using an inverted light microscope (Nikon, Tokyo, Japan) as described previously [ 37 ]. Cell survival was analyzed with a trypan blue exclusion method as described previously [ 38 ]. After treatment with MPP, rat calvarial osteoblasts were trypsinized with 0.1% trypsin-ethylenediaminetetraacetic acid (EDTA) (Gibco-BRL).…”
Section: Methodsmentioning
confidence: 99%
“…Then, primary rat osteoblasts were treated with 25, 50, and 100 μM MPP for 24 h or 100 μM MPP for 6, 12, and 24 h. Morphologies of osteoblasts were observed and photographed using an inverted light microscope (Nikon, Tokyo, Japan) as described previously [ 37 ]. Cell survival was analyzed with a trypan blue exclusion method as described previously [ 38 ]. After treatment with MPP, rat calvarial osteoblasts were trypsinized with 0.1% trypsin-ethylenediaminetetraacetic acid (EDTA) (Gibco-BRL).…”
Section: Methodsmentioning
confidence: 99%
“…The authors have demonstrated that the bradykinin/BDKRB1 increased the aqp4 expression through BDKRB1 mediated Ca2+ influx, which induces MEK4 phosphorylation and, consequently the downstream ERK1/2-NF-κB induction both in vitro and in vivo in human and murine cells. Overall, these data have suggested the key-role of bradykinin-BDKRB1-aqp4 action on cytoskeleton and morphological changes, as GBM oedema formation and its invasive and migratory power [128].…”
Section: Resistance To Temozolomidementioning
confidence: 75%
“…NFkB may drive mesenchymal conversion by controlling the expression of genes associated with a mesenchymal program such as Signal Transducer and Activator of Transcription (STAT) 3 and CCAAT-enhancer-binding protein B (C/EBPB) [ 55 ]. NFkB is constitutively activated in glioma stem cell patient lines and GBM mouse models and has an essential role in controlling GBM pathobiology [ 56 , 57 , 58 , 59 ]. Thus, a mesenchymal state enhances GBM migration and therapy resistance, and can, paradoxically, be created in response to chemo-radiotherapy.…”
Section: The Identity Of the Tumor Cells In The Peritumoral Zonementioning
confidence: 99%
“…The invasion is possibly mediated through the IL8 activation of NFkB [ 113 ]. Additionally, bradykinin binding to BKR2 both increases intracellular calcium to support cytoskeletal remodeling as well as activates the NFkB pathway to promote migration of GBM cells [ 58 , 109 ]. This suggests that specialized GBM can migrate across blood vessels in response to chemoattractants secreted by endothelial cells.…”
Section: The Right Niche To Subsist In the Peritumoral Zonementioning
confidence: 99%